The novel OMERACT Ultrasound Scoring System for salivary glands changes in patients with Sjögren's syndrome is associated with MRI and salivary flow rates - MUMCU, GONCA; ÇİMŞİT, CANAN (My University, 2023)
Objective To assess the construct validity of the novel Outcome Measures in Rheumatology (OMERACT) ultrasound (US) semiquantitative scoring system for morphological lesions in major salivary glands by comparing it with magnetic resonance imaging (MRI) and unstimulated whole salivary flow rates (U-WSFRs) in patients with primary Sjögren syndrome (pSS). Methods Nine sonographers applied the OMERACT 0-3 grayscale scoring system for parotid (PGs) and submandibular glands (SMGs) in 11 patients with pSS who also had MRIs performed. These were evaluated by 2 radiologists using a semiquantitative 0-3 scoring system for morphological lesions. The agreement between US and MRI and the association between U-WSFRs and imaging structural lesions was determined. A score ≥ 2 for both US and MRI was defined as gland pathology. Results The prevalence of US morphological lesions in 11 patients with a score ≥ 2 was 58% for PGs and 76% for SMGs, and 46% and 41% for PGs and SMGs, respectively, for MRI. The agreement between OMERACT US scores and MRI scores was 73-91% (median 82%) in the right PG and 73-91% (median 91%) in the left PG, 55-91% (median 55%) in the right SMG and 55-82% (median 55%) in the left SMG. When relations between the presence of hyposalivation and an US score ≥ 2 were examined, agreement was 91-100% (median 83%) in both PGs and 55-91% (median 67%) in both SMGs. Conclusion There is moderate to strong agreement between the OMERACT US and MRI scores for major salivary glands in patients with pSS. Similar agreement ratios were observed between the higher OMERACT US scores and presence of hyposalivation.